Neutron attenuation in GNP-reinforced B4C-TiB2 composites: Integrated experimental and MCNP6.2 simulation analysis - Kamislioglu, Mirac; Erbay, Onur; Uygun, Berkay; Aydogmus, Demet; Ayas, Erhan; Buyuk, Bulent; Calisir, Bircan (Pergamon-Elsevier Science Ltd, 2026)
This study investigates the neutron radiation attenuation properties of B4C-TiB2 reference composites and B4C-TiB2-GNP composites reinforced with 1, 2, and 3 vol% graphene nanoplatelets (GNP), fabricated via Spark Plasma Sintering (SPS). B4C offers excellent neutron shielding owing to its unique absorption property, while TiB2 and GNP additions to B4C can further enhance its shielding capability due to their combined density enhancement effects. Neutron transmission tests were carried out using a Nuclear-Chicago Howitzer-3 (NH-3) equipped with a 5-Ci 239Pu-Be neutron source. The total macroscopic cross-section (Sigma Tot) values determined for the GNP-reinforced B4C-TiB2 composites were investigated. Among them, the sample containing 1 vol% GNP exhibited a slightly higher Sigma Tot value compared to the other compositions. Thermal neutron attenuation was also evaluated through MCNP6 Monte Carlo simulations to validate experimental data. A strong correlation between simulated and measured results confirms the accuracy and consistency of the adopted methodology, and the results align with established literature. The findings demonstrate the promising potential of GNP-reinforced B4C-TiB2 composites as multifunctional materials for advanced nuclear radiation shielding applications, particularly in the energy sector, as well as in the aerospace and defense sectors.
Keywords: GNP-Reinforced B2C-TiB2 composites; Neutron radiation; Neutron howitzer Pu-(239-Be) source; Thermal neutrons; Detection system